The Attractiveness of Blended Learning in the 21st Era in Higher Education - Nofirman, Nofirman; Salong, Amjad; Rachman, Azhariah; Zulkarnain, Ihwan; Bangun, Eka Uliyanti Putri br (Al-Hijr: Journal of Adulearn World, 2024)
The face-to-face learning process in the classroom has lost its appeal in this 21st era. The development of technology in the era of the industrial revolution 4.0 requires an educator to innovate in packaging the teaching and learning process to be more efficient and interesting. The learning process must prioritize skills. Learning in higher education is required to emphasize aspects of creativity and innovation, critical thinking and problem solving, communication and collaboration. Learning in higher education requires lecturers and students to always be open and invite students to do technology-based problem solving. This writing uses the literature review method. Literature review contains reviews, summaries, and written thoughts about several library sources (can be articles, books, slides, information, internet, etc.), about the topics discussed. Learning must be creative and innovative. Blended Learning can be an effective alternative and strategy, especially in universities. A learning innovation with the main goal of providing opportunities for various characteristics so that an independent, sustainable, lifelong learning process occurs so that learning will be effective, more efficient, interesting and fun.